Human fetal skin derived merkel cells display distinctive characteristics in vitro and in bio-engineered skin substitutes in vivo - Michalak-Micka, Katarzyna; Rütsche, Dominic; Mazzone, Luca; Büchler, Vanessa L.; Moehrlen, Ueli; Klar, Agnes S.; Biedermann, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
Human skin contains specialized neuroendocrine Merkel cells responsible for fine touch sensation. In the present study, we performed in-depth analysis of Merkel cells in human fetal back skin. We revealed that these Merkel cells expressed cytokeratin 20 (CK20), were positive for the neuroendocrine markers synaptophysin and chromogranin A, and the mechanosensitive ion channel Piezo2. Further, we demonstrated that Merkel cells were present in freshly isolated human fetal epidermal cells in vitro, and in tissue-engineered human dermo-epidermal skin substitutes four weeks after transplantation on immune-compromised rats. Merkel cells retained the expression of CK20, synaptophysin, chromogranin A, and Piezo2 after isolation and in culture, and in the skin substitutes after transplantation. Interestingly, we observed that in fetal skin and in skin substitutes, only Merkel cells were positive for CK8, while in culture, also non-Merkel cells showed positivity for CK8. In summary, human fetal Merkel cells showed phenotypical features confirming their cell identity. This findings are of pivotal importance for the future application of fetal tissue-engineered skin in clinics.